A comprehensive survey on simulators, emulators, and testbeds for VANETs. (17th February 2022) - Babu, Sarath; Raj Kumar P, Arun
Summary: Nowadays, inter‐vehicle and intra‐vehicle communication triggers the development of safety and non‐safety applications in Vehicular Adhoc NETworks (VANET). These applications need to be evaluated before the actual implementation. The performance of these applications is generally evaluated through indispensable tools such as simulators, emulators, and testbeds. Although simulators, emulators, and testbeds are available as open‐source or proprietary for VANET applications, finding the correct tool for the experiment is intriguing and challenging from the researcher's perspective. In this paper, our focus is to provide a comprehensive survey on the existing simulators, emulators, and real time testbeds based on technical specifications, capabilities, etc. To the best of our knowledge, there is no such an exhaustive survey that exists in the literature. Further, we developed a real time low‐cost VANET testbed on our institute campus to implement the VANET related projects. Abstract : The summary of the research work is as follows: Detailed discussion on the purpose‐wise suitability of VANET simulators including technical specification will pave a way for the researchers to select the appropriate simulator in conducting experiments in VANET; step‐by‐step implementation of conducting the VANET related real‐time experiments in our institute campus is explained and will definitely motivate the researcher to develop a low‐cost testbed for validating the proposed algorithms/novel ideas.